2018
DOI: 10.1016/j.micpath.2018.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the tri-dimensional effect of endophytic Streptomyces sp. on chickpea for plant growth promotion, helper effect with Mesorhizobium ciceri and host-plant resistance induction against Botrytis cinerea

Abstract: A total of 219 endophytic actinobacteria, isolated from roots, stems and leaves of chickpea, were characterized for antagonistic potential against Botrytis cinerea, causal organism of Botrytis grey mold (BGM) disease, in chickpea. Among them, three most potential endophytes, AUR2, AUR4 and ARR4 were further characterized for their plant growth-promoting (PGP) and nodulating potentials and host-plant resistance against B. cinerea, in chickpea. The sequences of 16 S rDNA gene of the three endophytes were matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…against R. solani in tomato ; Streptomyces sp. against Botrytis cinerea in chickpea (Vijayabharathi et al 2018). It is concluded that the enhancement of the antioxidants upon inoculation of BCA-696 would have enhanced the charcoal rot disease resistance levels in sorghum against M. phaseolina.…”
Section: Discussionmentioning
confidence: 96%
“…against R. solani in tomato ; Streptomyces sp. against Botrytis cinerea in chickpea (Vijayabharathi et al 2018). It is concluded that the enhancement of the antioxidants upon inoculation of BCA-696 would have enhanced the charcoal rot disease resistance levels in sorghum against M. phaseolina.…”
Section: Discussionmentioning
confidence: 96%
“…Beneficial endophytic actinobacteria with potential biocontrol characteristics have been previously isolated from diverse plant species, such as tomato (Passari et al, 2016a), cereal crops (Patel et al, 2018), and legumes (Le et al, 2016;Vijayabharathi et al, 2018). Endophytic actinobacteria augment plant growth directly through nutrient solubilization, modulation of hormone levels, nitrogen fixation (Palaniyandi et al, 2013;Golinska et al, 2015;Figueiredo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Often, these rhizospheric microbes individually or in consortia produce a wide variety of secondary metabolites that are known to aid in plant growth under stressful conditions (Musilova et al 2016). Inhibition of M. phaseolina growth by these Streptomyces strains is mainly attributed to their ability to produce anti-fungal compounds such as hydrolytic enzymes and acids (Alekhya and Gopalakrishnan 2017;Vijayabharathi et al 2018;Kim et al 2019). These PGPR strains are mainly regarded as bio-control agents as they potentially produce chitinase, siderophore and hydrocyanic acid (HCN) which confer disease resistance in crops such as wheat (Kumar et al 2018) and tomato (Abo-Elyousr et al in the present study were previously reported to produce chitinase, siderophore and HCN (Gopalakrishnan et al 2011a;Sreevidya et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…and M. phaseolina exhibited significantly enhanced antioxidant compounds including superoxide dismutase, catalase, ascorbate peroxidase, guaiacol peroxidase, glutathione reductase, phenylalanine ammonia-lyase, polyphenol oxidase and total phenolic contents over shoot samples treated with only M. phaseolina. Numerous studies have reported a significant increase in the antioxidant enzymes and total phenolic contents in crops when beneficial microbes including Streptomyces were introduced to fight off the pathogen infection Rais et al 2017;Vijayabharathi et al 2018;. Therefore, it appears that the five strains of Streptomyces, CAI-17, KAI-26, KAI-27, MMA-32 and SAI-13, enhanced the expression of defence-related enzymes to combat against the M. phaseolina infection.…”
Section: Sai-13mentioning
confidence: 99%